Portable Heritage: perspectives on white mobility in post-apartheid South Africa - Le Riche, Pierre Henri (Michaelis School of Fine Art, 2024)
This written component partially fulfils the special requirements for the Master of Fine Arts degree as specified by the University of Cape Town. The content of this document, which is intentionally concise, offers contextualisation and supplementation to my visual research. It must be stressed that this research is not the primary object offered for examination; that important role lies with my body of artworks that work in conjunction with the document. The goal of this document is to locate my practice within a broader field of artistic research, which is achieved through the consideration of relevant theorists and artists working within the same scope as I do. The visual material I reference in this document are catalogued using a captioning system that states the name of the artist or photographer, the title of the work, medium and date of completion, whilst throughout the rest of the document the Harvard (author - date) system is employed as a means of reference.